Implementation of STEM-Based Inquiry in Learning Fundamental Laws of Chemistry: Students’ Perception and Response - Pohan, Lisa; Retno Dwi Suyanti; Asep Wahyu Nugraha; Dwi Pebrianti; Rahmadatina Panjaitan; Selamat Husni Hasibuan (Jurnal Pendidikan IPA Indonesia, 2024)
This research aims to analyze students' perceptions and responses to STEM-based inquiry learning. This research used a quantitative and qualitative survey method. The subjects of this study were 25 first-semester students who took the General Chemistry course in the chemistry education study program. The research instruments used were questionnaires, interviews, and learning observation sheets. Meanwhile, the quantitative technique used is descriptive analysis. Quantitative data analysis found that 72% of students were actively involved in learning when formulating questions and investigations. STEM-based inquiry learning in observing, measuring, and analyzing data helped 72% of students understand the basic laws of chemistry. Most students benefit from STEM-based inquiry learning because this model triggers curiosity, the ability to formulate scientific questions, and the ability to evaluate and utilize information that helps determine experimental procedures. In conclusion, the learning experience using the STEM-based inquiry learning model on the basic laws of chemistry positively impacts students' perceptions and responses.